KORELASI ANTARA VARIASI PEMADATAN TERHADAP NILAI STABILITAS MARSHALL PADA LASBUTAG CAMPURAN PANAS - Alamsyah, Alik Ansyori (Department of Civil Engineering, Faculty of Engineering, University of Muhammadiyah Malang, 2012)
Alik Ansyori AlamsyahJurusan Teknik Sipil – Fakultas TeknikUniversitas Muhammadiyah MalangAlamat Korespondensi : Jl. Raya Tlogomas, No.246 MalangEmail: alik.syah@yahoo.comABSTRACTAsbuton is one type of natural asphalt from Buton island. How to use existing asbuton diverseas Lasbutag (Buton Asphalt Layers Beragregat) cold mix or ACAS (Aggregate Cold Abuton Sheet),or hot mix Asbuton Ahaz (Aggregate Asbuton Hot Sheet), a hot mixture of non-aggregate AsbutonNahas (Non Aggregate Asbuton Hot Sheet ) and non-aggregate mixture to cool Asbuton NACAS(Non aggregate cold Asbuton Sheet).LASBUTAG marshall stability value in the hot mixture showed no variation of the initial valuebefore the collision modifier of 244.772 kg at 3.6%: 50%, while the modifier 3.6%: 216.733 75% invalue, where the stability is eligible for the low traffic . To be used for medium and heavy traffic, thecollision is carried out at 49.5 and 224.6. In the hot mixture LASBUTAG modifier composition3.6%: 75%, the collision is carried out for 105 and traffic is heavy at 395. VIM on both compositionsare still relatively large and showed a decrease with increasing stability in LASBUTAG hot mixture.VMA qualified on both the composition of the modifier, above 16%. Flow on LASBUTAG hotmixture showed a trend to decline with the collision. From the test results and analysis show thatthe compaction of different variations affect the stability of the marshal.Keywords: Lasbutag, Variations Compaction, Mixed Heat